Optimizing Link-Level Entanglement Generation in Quantum Networks with Unequal Link Lengths - Poramet Pathumsoot (2022)
Quantum internet offers a variety of applications that either enhance or surpass its classical counterpart. Quantum repeaters are imperative to a quantum network as they connect between two quantum nodes, and create quantum entanglement between two targeted nodes with entanglement swapping protocol which require resource from both connections. As a quantum state has a finite decoherent time, it is crucial that a connection protocol is performed efficiently and within suitable time interval, so that two end-To-end matter qubits are entangled. We simulate a second generation network of quantum repeaters, one that is capable of quantum error correction, to estimate the waiting time needed to establish connection between distant nodes. Simulations are performed for a linear chain of nodes with unequal path lengths, and loss rates. We find that asymmetry of path lengths contributes to the waiting time of physical qubits. By simply adjusting the photon generation rate from one of its nodes, the waiting time is reduced while the time to complete quantum state tomography remains unaffected. This simple adjustment can play important roles in compensating for distance asymmetry when a quantum repeater is not stationary.